Поверхностные плазмоны запасают солнечную энергию - Шварц, К.; Даулетбекова A.; Сорокин, М. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Surface plasmons store solar energy